Application of Case-Based Learning Model on Science-11 Class Learning Outcomes on Digestive System Disorders - Annida Rizka Aulia; Aminuddin Prahatama Putra; Aulia Ajizah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Applying an appropriate learning model affects learning quality because it can improve learning activities in the classroom and strengthen students' understanding to achieve learning objectives. This study aims to determine the effect of applying the case-based learning model on students’ cognitive, affective, and psychomotor learning outcomes and explain the response of science-11-grade students to the application of CBL in learning digestive system disorders. The subjects were 66 students from XI MIPA 1 (Control class) and XI MIPA 3 (treatment class) with the Quasi Experiment method. From the research results, it was concluded that there was a significant effect of CBL on cognitive product learning outcomes at the first and second meetings with a Sig. (2-tailed) 0.000 < 0.05. The N-gain value of experimental class students' cognitive product shows increased learning outcomes after learning with the CBL model. By applying the CBL model, cognitive process learning outcomes in the experimental class were higher than in the control class. Applying the CBL learning model affects affective and psychomotor learning outcomes and increases the positive response to 95.45%. The average percentage of student response questionnaire scores was 76.37%, meaning that students agreed that applying the CBL model can support their learning on digestive system disorders